A vida nos olhos, o coração nas mãos: concepções e representações femininas do processo saúde-doença Life in their eyes, heart in their hands: conceptions and representations of women in the process of health and disease - Glauce Dias; Sylvia do Carmo Castro Franceschini; José Roberto Reis; Roberta Sena Reis; Rodrigo Siqueira-Batista; Rosângela Minardi Mitre Cotta (História, Ciências, Saúde: Manguinhos)
A abordagem histórico-social das representações de saúde e doença das mães do município de Teixeiras (MG) visa compreender as condutas nessa esfera e o desenvolvimento de pesquisas em saúde coletiva. Construíram-se atrativos semânticos e indicadores para uma visão pluralista de saúde-doença. A busca da felicidade foi apresentada como um conceito de saúde pelas mães, retomando aspectos filosóficos aristotélicos e espinosistas, mas elas deram mais destaque à ausência da doença. o modelo assistencial hegemônico fornece ainda fortes referenciais para interpretar tais experiências. Como a condição cuidadora da mãe facilita a compreensão de outros fatores que afetam o processo saúde-doença, é possível planejar ações de saúde menos alienantes e mais libertárias. This social and historical investigation into the ways the health and sickness of mothers from Teixeiras municipality, Minas Gerais state, was represented is designed to comprehend behaviors in this sphere and help develop research in collective health. The semantics and indicators of a pluralistic view of disease and health, were built up from the most holistic to the most biomedical, from the most relational to the most individual. The quest for happiness was presented as a health concept by the mothers, which recalls Aristotelian and Spinozian philosophical concepts, but they put greater emphasis on the absence of illness. The prevailing welfare model still supplies useful references for interpreting such experiences. As the mother's status as care-taker helps one glean an understanding of other factors that affect the process of health and disease, it becomes possible to plan healthcare initiatives that are less alienating and more libertarian.